Role of Bacterial Lipopolysaccharide in Enhancing Host Immune Response to Candida albicans - Helen Rogers; David W. Williams; Gui-Jie Feng; Michael A. O. Lewis; Xiao-Qing Wei (Clinical and Developmental Immunology)
Human infections involving yeast of the genus Candida often occur in the presence of bacteria, and, as such, it is important to understand how these bacteria influence innate host immunity towards Candida. Dectin-1 is a cell receptor of macrophages for Candida albicans recognition. The aim of this study was to examine dectin-1 expression by monocytes after stimulation with bacterial lipopolysaccharide (LPS), followed by heat-killed C. albicans (HKC). Freshly isolated human peripheral blood monocytes (PBMCs) and human monocytes cell line (THP-1) cells expressed low levels of dectin-1. Stimulation with LPS and GM-CSF/IL-4 was found to increase dectin-1 expression in both CD14+ human PBMC and THP-1 cells. Enhanced dectin-1 expression resulted in increased phagocytosis of Candida. When THP-1 cells were challenged only with HKC, detectable levels of IL-23 were not evident. However, challenge by LPS followed by varying concentrations of HKC resulted in increased IL-23 expression by THP-1 cells in HKC dose-dependent manner. Increased expression of IL-17 by PBMC also occurred after stimulation with Candida and LPS. In conclusion, bacterial LPS induces an enhanced immune response to Candida by immune cells, and this occurs through increasing dectin-1 expression.